Unilateral Incomplete Double Ureter at NMCTH - Bhatta, P; Bastola, R; Gurung, P; Gyawali, M (Med Phoenix, 2018)
The anomalies associated to the duplications of ureter and kidneys result from an early division of ureteric diverticulum. Duplex collecting system is presence of two pylocaliceal system which is associated with single or double ureter. Bifid ureter is one of the variations related to congenital anomalies of urinary system which are often an incidental finding. Surgeons performing surgeries in pelvic region should be aware of such anomalies remain asymptomatic, incidentally found, sometimes present with pyelonephritis / calculi. Med Phoenix. Vol. 3, Issue. 1, 2018, Page: 89-90